(untitled) (Tanzania Journal for Population studies and Development, 2023)
This study examined the extent to which students at the St. John’s University in Dodoma use information and communication technology (ICT) in learning. A quantitative research design was employed, utilizing the survey method to collect data. Convenience sampling was used to select 110 respondents whose e-mails were obtained. Data was analysed using the Statistical Package for Social Sciences (SPSS). The chi-square test was utilized to explore the relationship between certain variables, while the Spearman t-test was employed to determine the correlation between students’ use of ICT in learning and their search competences. The key findings indicate that students at St. John’s University have a high level of ICT usage in their learning endeavours, despite some inadequacies in the available learning facilities. Moreover, gender does not significantly influence the application of ICT in learning. Additionally, there was no significant relationship found between the use of ICT in learning and students’ competences in search skills. The study reveals that students heavily rely on both audio-visual materials and online textual resources. Based on the findings, it is recommended that the St. John’s University continues to enhance its ICT infrastructure to facilitate effective access and utilization of information by students. Libraries should allocate sufficient funds for the subscription of mostly electronic resources along with print resources.